Activity of Antioxidant System in Patients with Uterine Fibroids - A. , Andreeva Ya; M., V. Labzina; L., Y. Labzina; A., S. Nechaykin; I., V. Abrashina; L., V. Zotova (International Journal of Psychosocial Rehabilitation, 2020)
Uterine fibroids are one of the most common benign tumors of the female reproductive system [1]. According to modern concepts, uterine fibroids are defined as a benign, non-specific hyperplastic process in the myometrium, in the pathogenesis of which a number of factors take part [2]. Nowadays the hormonal theory in the etiology of the growth and occurrence of uterine fibroids is the most relevant [3]. A number of authors connect the growth of fibroids with an increased level of estrogen that develops in the tissues of the tumor itself [4]. Recently, the role of endogenous intoxication as the main pathogenic mechanism of the development of this disease has been studied in detail. Researches aimed at studying this problem prove that all the main pathophysiological manifestations of endogenous intoxication are determined by a destruction of structural and functional organization of the membranes, which ultimately leads to destabilization and disruption of cell growth and division.